Potential use of Spirulina sp. as fish feed : A mini review - Prameswari, Rhiana; Andriani, Yuli; Gumilar, Iwang; Hasan, Zahidah (Aceh Journal of Animal Science, 2024)
Spirulinasp. is one of the microalgae that is used as natural food for fish seeds or larvae. Spirulina sp. contains 6071% protein, 8% fat, 16% carbohydrates, and vitamins as well as 1.6% Chlorophyll-a, 18% Phycocyanin, 17% -Carotene, and 2030% -linoleaic acid from total fatty acids. Cultivation of Spirulina sp. can be done using organic media and inorganic media. The types of inorganic media that can be used are Urea, TSP, Zarrouk, Conwy and Walne, while the organic media that can be used are vermicompost, quail droppings, guano, liquid waste from banana stems, coconut husks, canna plants, fermentedAzolla pinnata, and bioslurry . The cultivated Spirulina can be used as fish feed in either fresh or dried form. Several research results show that giving Spirulina sp. flour had a significant effect (P0.05) on the growth and brightness of fish color with additional concentrations in the range of 1.2-10 grams/100 grams of feed